2017
DOI: 10.1101/197921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired phloem loading in genome-edited triple knock-out mutants of SWEET13 sucrose transporters

Abstract: One Sentence Summary: Three SWEET sucrose transporter paralogs are necessary for phloem loading in maize.All rights reserved. No reuse allowed without permission.was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint (which . http://dx.doi.org/10.1101/197921 doi: bioRxiv preprint first posted online Oct. 3, 2017; 2 SummaryCrop yield depends on efficient allocation of sucrose from leaves to seeds. In Arabidop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Many SWEETs have been shown to transport glucose and/or sucrose, and even the bacterial ancestors are sugar transporters (Chen et al, 2015a). SWEET mutant phenotypes are consistent with physiological roles in sugar transport during nectar secretion, phloem loading and seed filling (Chen et al, 2012;Lin et al, 2014;Sosso et al, 2015;Bezrutczyk et al, 2017;Yang et al, 2017). However, Shiping Wang's lab indicated that a number of SWEETs did not complement a yeast sugar transport mutant (Yuan et al, 2014).…”
Section: Sweets --Selective Sugars Transporters or Transporters Of Otmentioning
confidence: 99%
See 1 more Smart Citation
“…Many SWEETs have been shown to transport glucose and/or sucrose, and even the bacterial ancestors are sugar transporters (Chen et al, 2015a). SWEET mutant phenotypes are consistent with physiological roles in sugar transport during nectar secretion, phloem loading and seed filling (Chen et al, 2012;Lin et al, 2014;Sosso et al, 2015;Bezrutczyk et al, 2017;Yang et al, 2017). However, Shiping Wang's lab indicated that a number of SWEETs did not complement a yeast sugar transport mutant (Yuan et al, 2014).…”
Section: Sweets --Selective Sugars Transporters or Transporters Of Otmentioning
confidence: 99%
“…Each plant contains about two dozen SWEET paralogs, which predominantly transport hexoses or sucrose. Of note, several SWEETs play critical roles in the cellular efflux of sugars, in phloem (AtSWEET11, 12, ZmSWEET13a, b, and c; Chen et al ., ; Bezrutczyk et al ., ), seeds (AtSWEET11, 12 and 15; OsSWEET11 and 15; Chen et al ., ; Yang et al ., ) and nectaries (AtSWEET9, BrSWEET9 and NtSWEET9; Lin et al ., ). In the context of pathogen susceptibility (discussed below), the efflux of sucrose in uninfected leaves by SWEETs appears to be limited to phloem parenchyma cells, at least in Arabidopsis.…”
Section: Suts Sweets and Stps: Gate Keepers Of Sugar Allocationmentioning
confidence: 99%
“…10); SWEET genes are proposed to efflux sucrose to the phloem apoplasm (Braun et al, 2014). In particular, SWEET13, 332 which was strongly affected in our study, has been previously singled out as a target 333 for crop improvement in maize (Bezrutczyk et al, 2017). In explaining elevated cadmium and salt, through antioxidant mechanisms (Brychkova et al, 2008), and 345 jasmonic acid and ABA signalling (Takagi et al, 2016).…”
mentioning
confidence: 99%
“…The possibility that SWEETs determine plant susceptibility or resistance by the control of nutrient provision to pathogens has recently been discussed (Chen et al, 2010; Bezrutczyk et al 2017; Breia et al, 2021). AtSWEET11 is a member of the clade III of the SWEET genes, involved in disease development (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%